2017
DOI: 10.1113/jp273480
|View full text |Cite|
|
Sign up to set email alerts
|

Refuting the myth of non‐response to exercise training: ‘non‐responders’ do respond to higher dose of training

Abstract: Key pointsr The prevalence of cardiorespiratory fitness (CRF) non-response gradually declines in healthy individuals exercising 60, 120, 180, 240 or 300 min per week for 6 weeks.r Following a successive identical 6-week training period but comprising 120 min of additional exercise per week, CRF non-response is universally abolished.r The magnitude of CRF improvement is primarily attributed to changes in haemoglobin mass. r The potential for CRF improvement may be present and unveiled with appropriate exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
264
2
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(288 citation statements)
references
References 57 publications
16
264
2
6
Order By: Relevance
“…Other reports have demonstrated a doseresponse relationship between exercise and reductions in blood pressure [36] and inflammation [37] in these same postmenopausal women, with the highest dose being the most effective (up to 200 min/week, which is 50 min longer than the dose currently recommended in the USA for producing substantial health benefits according to physical activity guidelines [38]). In agreement, a recent report determined that response to a dose eliminates non-response in V O 2peak of healthy individuals [7]. Such a high volume of exercise training, however, may not be feasible or practical for all individuals.…”
Section: Exogenous Factors Also Influence Non-response To Exercisesupporting
confidence: 67%
See 1 more Smart Citation
“…Other reports have demonstrated a doseresponse relationship between exercise and reductions in blood pressure [36] and inflammation [37] in these same postmenopausal women, with the highest dose being the most effective (up to 200 min/week, which is 50 min longer than the dose currently recommended in the USA for producing substantial health benefits according to physical activity guidelines [38]). In agreement, a recent report determined that response to a dose eliminates non-response in V O 2peak of healthy individuals [7]. Such a high volume of exercise training, however, may not be feasible or practical for all individuals.…”
Section: Exogenous Factors Also Influence Non-response To Exercisesupporting
confidence: 67%
“…In one report, the investigators found that V O 2peak non-response was abolished after increasing the exercise dose in healthy individuals [7]. While these data are strong in terms of V O 2peak as the response variable, other important response variables known to be improved by exercise training were not assessed (e.g.…”
Section: Does Non-response To Exercise Actually Exist?mentioning
confidence: 99%
“…). In the only study to investigate the effect of different volumes of training on Mito VD , increasing training volume (by increasing days of weekly training from 1 to 4) led to greater increases in Mito VD (there was no further increase when training volume was increased further by training 5 days per week) (Montero & Lundby, ). In the only study to directly compare the effects of different training intensities, Mito VD increased by 47% following SIT and 88% following MICT (although this difference between groups was not significant; Shepherd et al .…”
Section: Relationship Between Training Volume and Training‐induced Chmentioning
confidence: 97%
“…In this issue of The Journal of Physiology , Montero and Lundby () subjected a large number of healthy young men ( n = 78) to an intense programme of endurance training. The subjects were divided into five groups and trained one, two, three, four or five days per week for 6 weeks.…”
Section: How To Resolve This Controversy?mentioning
confidence: 99%